2021
DOI: 10.1002/sctm.20-0431
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Huntington's Disease Mouse Model to Assess the Role of Neuroinflammation on Disease Progression and to Develop Human Cell Therapies

Abstract: Huntington's disease (HD) is a fatal autosomal-dominant neurodegenerative disease caused by a trinucleotide CAG repeat expansion of the huntingtin gene (HTT) that affects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…McGinley et al used oral immune suppression of an Alzheimer’s disease model to characterize and evaluate the efficacy of human cortical neural stem cells engineered to express insulin-like growth factor 19 . Our group used immune suppression delivered by subcutaneously implanted Alzet osmotic pumps 28 prior to creating immune deficient mouse models to test cellular therapies for Huntington’s disease 16 . Similarly, immune deficient models of Angelman syndrome 29 and Sandhoff disease have been created to test the efficacy of gene modified human hematopoietic stem cells in relevant disease models 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…McGinley et al used oral immune suppression of an Alzheimer’s disease model to characterize and evaluate the efficacy of human cortical neural stem cells engineered to express insulin-like growth factor 19 . Our group used immune suppression delivered by subcutaneously implanted Alzet osmotic pumps 28 prior to creating immune deficient mouse models to test cellular therapies for Huntington’s disease 16 . Similarly, immune deficient models of Angelman syndrome 29 and Sandhoff disease have been created to test the efficacy of gene modified human hematopoietic stem cells in relevant disease models 30 .…”
Section: Discussionmentioning
confidence: 99%
“…To determine the presence of immune cells in the MPSIIIA-TKO strain, spleens were collected and labeled with antibodies specific for mouse immune cell markers and analyzed by flow cytometry following a previously published protocol 16 . Mice were euthanized by CO 2 asphyxiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first of our Featured Articles published this month in STEM CELLS Translational Medicine, Dahlenburg et al describe the generation and characterization of an immunodeficient mouse model of Huntington's disease and the subsequent development of a humanized strain to define how the human immune system impacts pathogenesis. 6 In a Related Article published in STEM CELLS, Yoon et al demonstrated how the intracerebral transplantation of clinical-grade neural stem cells (NSCs) in a rat model of Huntington's disease prompted significant improvements in behavioral and pathological deficits by replacing lost cells and inducing endogenous regeneration. 7 MicroRNAs (or miRNAs) are short noncoding RNAs of 20 to 25 nucleotides in length that constitute a crucial part of the posttranscriptional regulatory machinery that fine-tunes gene expression.…”
mentioning
confidence: 99%